A EDUCAÇÃO DAS RELAÇÕES ÉTNICO-RACIAIS E A FORMAÇÃO DO ESTUDANTE DE DIREITO: UM ESTUDO SOBRE OS CURSOS DE DIREITO DAS UNIVERSIDADES DO ESTADO DO RIO GRANDE DO SUL - Neves, Veronica de Jesus Prince (2022)
The dissertation is part of the Research Line Teaching, Epistemologies and Teacher Training of the Master's in Teaching Humanities and Languages. Its research focus was on the formation of the student in Law and the Education of Ethnic-Racial Relations in Law Courses. In this way, the following research problem was defined: how do the Undergraduate Law Courses in the State of RS contemplate the education of ethnic-racial relations in the formation of the student? Therefore, the general objective was listed: to analyze how the Undergraduate Law Courses of the State of RS contemplate the education of ethnic-racial relations in the formation of the student, and in a specific way: a) to recognize the public policies on the education of ethnic-racial relations in higher education; b) investigate the trajectory of Brazilian higher education and the educational implications of ethnic-racial relations in higher education; c) to analyze the National Curriculum Guidelines for the Education of Ethnic-Racial Relations, and d) to investigate how the education of ethnic-racial relations is contemplated in the curricular matrices of the Law Course. The research approach is qualitative. For that, documental research was chosen. The data collection procedures were the menus and/or discipline programs of the Law courses of the Universities of the State of Rio Grande do Sul. In the analysis of the data obtained for this investigation, the Discursive Textual Analysis (DTA) proposed by Moraes (2003) was used. Race, Ethics and Citizenship. After analyzing and interpreting the data, the results showed that such categories are structuring elements when it comes to the Education of Ethnic-Racial Relations in the formation of the law student.